Triclosan: Current status, occurrence, environmental risks and bioaccumulation potential - Dhillon, Gurpreet Singh (2015)
Triclosan (TCS) is a multi-purpose antimicrobial agent used as a common ingredient in everyday household personal care and consumer products. The expanded use of TCS provides a number of pathways for the compound to enter the environment and it has been detected in sewage treatment plant effluents; surface; ground and drinking water. The physico-chemical properties indicate the bioaccumulation and persistence potential of TCS in the environment. Hence, there is an increasing concern about the presence of TCS in the environment and its potential negative effects on human and animal health. Nevertheless, scarce monitoring data could be one reason for not prioritizing TCS as emerging contaminant. Conventional water and wastewater treatment processes are unable to completely remove the TCS and even form toxic intermediates. Considering the worldwide application of personal care products containing TCS and inefficient removal and its toxic effects on aquatic organisms, the compound should be considered on the priority list of emerging contaminants and its utilization in all products should be regulated.